1977
DOI: 10.1002/jss.400060108
|View full text |Cite
|
Sign up to set email alerts
|

The transport of lysosomal enzymes

Abstract: This paper reviews the experimental evidence for the proposal that hydrolytic enzymes are introduced into lysosomes of cultured fibroblasts only after secretion and receptormediated recapture.Key words: lysosornes, lysosomal enzymes, pinocytosis, secretion, of-biduronidase How are hydrolytic enzymes transferred from the site of their synthesis to lysosomes? In the usual concept of lysosome formation, the hydrolases proceed from rough t o smooth endoplasmic reticulum, then either t o the Golgi apparatus or t o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0
1

Year Published

1978
1978
1986
1986

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(60 citation statements)
references
References 35 publications
2
57
0
1
Order By: Relevance
“…According to the Hickman-Neufeld hypothesis for transport of lysosomal enzymes in fibroblasts, these enzymes have to be secreted before they reach the lysosomes via a receptor-mediated recapture (Hickman & Neufeld, 1972;Neufeld et al, 1977). Selective prevention of lysosomal-enzyme recapture should result in an intracellular decrease and extracellular increase in lysosomal-enzyme activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Hickman-Neufeld hypothesis for transport of lysosomal enzymes in fibroblasts, these enzymes have to be secreted before they reach the lysosomes via a receptor-mediated recapture (Hickman & Neufeld, 1972;Neufeld et al, 1977). Selective prevention of lysosomal-enzyme recapture should result in an intracellular decrease and extracellular increase in lysosomal-enzyme activities.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of intracellular lysosomal-enzyme decrease would be determined by the intracellular half-life of these enzymes. Previous experiments have established a half-life of 9 days for fi-N-acetylglucosaminidase prepared from fibroblast secretions (Hickman & Neufeld, 1972;Neufeld et al, 1977) and even shorter half-lives for other lysosomal enzymes from non-fibroblast sources (Hickman & Neufeld, 1972;von Figura & Kresse, 1974). None of the conditions by which recapture of released lysosomal enzymes was prevented over a period of 12-21 days led to a decrease in intracellular lysosomal enzyme activities.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal enzymes can be secreted from fibroblasts into the extracellular space and then taken back to the cells. 15 " 17 Miller et al 1819 clearly showed that the soluble glycoproteins (named collectively epiglycanin) released by TA3 Ha tumor cells are shed from a surface-bound pool. Finally, Rogers et al 20 and Alt et al 21 have shown that the membrane-bound and secreted form of the n chain of IgM are coded for by different mRNA's and hence must be independently synthesized.…”
Section: Discussionmentioning
confidence: 99%
“…Neufeld et al (12) have postulated that extracellular enzymes are selectively assimilated by a series of steps, including binding of the enzyme to the cell surface through carbohydrate residues, endocytosis, and, finally, fusion of the endocytotic vacuoles with the lysosomes. A human platelet ,B-glucuronidase (17), a human aiduronidase (18), bovine testicular ,8-galactosidase (19), and a variety of other human lysosomal enzymes (20) have been suggested as recognition imarkers for the selective uptake of the respective enzymes by fibroblasts.…”
Section: Introductionmentioning
confidence: 99%